2012
DOI: 10.1109/tit.2011.2176310
|View full text |Cite
|
Sign up to set email alerts
|

Fast-Decodable Asymmetric Space-Time Codes From Division Algebras

Abstract: Multiple-input double-output (MIDO) codes are important in the near-future wireless communications, where the portable end-user device is physically small and will typically contain at most two receive antennas. Especially tempting is the 4 × 2 channel due to its immediate applicability in the digital video broadcasting (DVB). Such channels optimally employ rate-two space-time (ST) codes consisting of (4 × 4) matrices. Unfortunately, such codes are in general very complex to decode, hence setting forth a call … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 33 publications
1
74
0
Order By: Relevance
“…£ The exact minimum determinant of this STBC has not been calculated, but it has been shown that the STBC has the NVD property [1]. ¥ These STBCs are not available explicitly in [1].…”
Section: 5mentioning
confidence: 99%
See 2 more Smart Citations
“…£ The exact minimum determinant of this STBC has not been calculated, but it has been shown that the STBC has the NVD property [1]. ¥ These STBCs are not available explicitly in [1].…”
Section: 5mentioning
confidence: 99%
“…Such a scenario occurs, for example, in the downlink transmission from a base station to a mobile phone, and in digital video broadcasting (DVB) where communication is between a TV broadcasting station and a portable TV device (see, for example, [14]). Of particular interest is the 4 × 2 MIDO system for which a slew of rate-2 STBCs have been developed [1], [2], [15]- [20], with the particular aim of allowing fast-decodability (see Definition 7), a term that was first coined in [15]. Among these codes, those in [1], [16]- [20] have been shown to have a minimum determinant that is bounded away from zero irrespective of the size of the signal constellation and hence STBC-schemes that consist of these codes have the NVD property and are DMToptimal for the 4 × 2 MIDO system [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fast-decodable codes are treated by Biglieri, Hong and Viterbo [15], Vehkalahti, Hollanti and Oggier [16], [17], Luzzi and Oggier [18], Markin and Oggier [19], and in [13], [14] and [9], to name just a few.…”
Section: Introductionmentioning
confidence: 99%
“…Fast decodable codes (codes that admit FSD) have reduced SD complexity owing to the fact that a few of the variables can be decoded as single symbols or in groups if we condition them with respect to the other variables. Fast decodable codes for asymmetric systems using division algebras have been recently reported [11]. Golden code and Silver code are also examples of fast decodable codes as shown in [12] and [13].…”
Section: Introductionmentioning
confidence: 99%